Innovations Ability Influenced by Creativity, Competence, and Intrinsic Motivation and Its Implications for Entrepreneurs Success - Wahyuningsih, Dian (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
The strategic issue that is currently trending in Small Business activities is making MSMEs the backbone of the national economy. Empowerment and development of the existence of small business centers are very necessary so that they can grow and be sustainable, especially in the fashion sector. This research aims to explain the ability to innovate which is influenced by creativity, competence, and intrinsic motivation, and its implications for the success of small entrepreneurs (survey of small entrepreneurs in the fashion sector throughout Greater Bandung). The type of research is quantitative research, the research method used is descriptive and verification methods, and research variables include Creativity, Competence and Intrinsic Motivation, Ability to Innovate, and Entrepreneurial Success. The total sample was 250 small business actors with data collection techniques using questionnaires. The data analysis technique uses structural equation modeling (SEM) with the LIESRELL program. Descriptive research results show that creativity, competence, intrinsic motivation, and the ability to innovate as well as the success of entrepreneurs fall into the moderate to good category. The results of the verification research show that creativity, competence, and intrinsic motivation influence the ability to innovate both simultaneously and partially and the ability to innovate influences the success of small entrepreneurs in the Greater Bandung fashion sector.